Time intervals in the pathway to diagnosis and treatment of patients with breast and gynecological cancer - Galindo, Blanca Sánchez; Sotos, Joseba Rabanales; González, Ángel López; Díaz, Marta Castaño; Martínez, Carmen María Sánchez; Hidalgo, Jesús López-Torres (Frontiers in Medicine, 2025)
BackgroundBreast and gynecological cancer have a high prevalence and a significant impact on public health. It is important to note that the time intervals until diagnosis and treatment influence the prognosis. The objective was to describe the delay in the diagnosis of breast and gynecological cancer and to identify the variables related to the patient, healthcare and the disease that intervene in the time interval until diagnosis and treatment.MethodsWe conducted a retrospective study (2014–2023) following a cohort of women with breast and gynecological cancer, from the onset of symptoms to the start of treatment. The study included 722 women from 30 general practice clinics in Albacete, Spain, and data were obtained from both primary care and hospital settings.ResultsAmong breast cancer patients, 150 (25.7%) had been diagnosed through screening, and among those diagnosed with cervical cancer, 14 (37.8%), it was not possible to calculate some time intervals. In breast cancer the variables associated with a total time interval (from first symptoms to start of treatment) of more than 90 days were: age over 50 and symptoms other than a breast lump. In gynecological cancer, the related variables were: no family history and having attended the health center for the first consultation. In the diagnostic interval (from first consultation to diagnosis), the variables associated with a duration of more than 30 days were: presenting with fewer than two risk factors in breast cancer and first consultation at the health center in gynecological cancer.ConclusionMost patients with breast and/or gynecological cancer are diagnosed in the early stages of the disease, except in the case of ovarian cancer. Most breast and cervical tumors are not diagnosed through screening. The time interval that most influences the total interval is the diagnostic interval, which includes the primary care interval. The treatment interval is high in most tumors, exceeding the recommended time. The results provide useful information for proposing improvements in access to diagnostic and therapeutic resources, as well as preferential referral circuits to improve early detection and prognosis of the disease.